The determinants of participation in a social program: Evidence from a prototypical job training program - James J Heckman; Jeffrey A. Smith (Institute for Labour Market Policy Evaluation (IFAU), 2003)
This paper decomposes the participation process of a prototypical program into eligibility, awareness, application, acceptance and enrollment. With this decomposition, we determine the sources of unequal participation for different groups, and demonstrate that variables often have very different effects at different stages in the participation process. Our analysis shows that personal choices substantially affect participation and that awareness of program eligibility is a major source of variation in participation.
Keywords: J24; 330; Social program participation; job training performance standards; cream skimming; job training partnership act (JTPA)